Kidney and pancreas transplantation a practical guide - Shoskes, Daniel A.; Srinivas, T. R. (Titte R.) (Current clinical urology, 2010)
The transplant physicians and surgeons at Cleveland Clinic have collaborated to produce, Kidney and Pancreas Transplantation: A Practical Guide. This volume is devoted to kidney and pancreas transplantation and is well grounded in scientific principles, quantitative clinical reasoning, clinical pharmacology, tested clinical practices and overall clinical applicability. Also addressed are key aspects in the initiation, maintenance and sustained growth of viable clinical programs in kidney and pancreas transplantation. Kidney and Pancreas Transplantation: A Practical Guide will be of great value to transplant physicians as well as medical and surgical fellows who intend to pursue an interest in transplantation.